2020
DOI: 10.24925/turjaf.v8i3.632-637.3109
|View full text |Cite
|
Sign up to set email alerts
|

Bazı Turp Çeşitlerinin Tuza Tolerans Düzeylerinin Belirlenmesi ve Tuzlu Koşullarda Çimlenme Üzerine Salisilik Asidin Etkinliğinin Değerlendirilmesi

Abstract: This study was conducted to determine tolerance levels of different radish varieties (white, black, red, little red radish) under salt stress conditions and to evaluate the effectiveness of exogenous salicylic acid (SA) application on germination and vegetative development. For this purpose; germination percentage (%), germination time (day), germination index calculated, and then number of leaves, shoot length (cm), root length (cm), leaf width (cm), leaf length (cm), stem diameter (mm), plant fresh and dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Likewise, in the study conducted by Shama et al (2016) on garlic, plant height, leaf fresh weight and leaf dry weight decreased with salt stress, and salicylic acid applications under salty conditions increased mentioned plant growth properties. In studies conducted on different vegetables, it was determined that salinity negatively affected plant growth, and salicylic acid applications under salty conditions had positive effects on plant growth parameters such as plant height, leaf length, plant fresh weight and plant dry weight (Qingmao et al, 2007;Yıldırım et al, 2008;Bukhat et al, 2020;Ulukapı et al, 2020). The results obtained in this study are in accordance with the findings in the literature.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, in the study conducted by Shama et al (2016) on garlic, plant height, leaf fresh weight and leaf dry weight decreased with salt stress, and salicylic acid applications under salty conditions increased mentioned plant growth properties. In studies conducted on different vegetables, it was determined that salinity negatively affected plant growth, and salicylic acid applications under salty conditions had positive effects on plant growth parameters such as plant height, leaf length, plant fresh weight and plant dry weight (Qingmao et al, 2007;Yıldırım et al, 2008;Bukhat et al, 2020;Ulukapı et al, 2020). The results obtained in this study are in accordance with the findings in the literature.…”
Section: Resultssupporting
confidence: 89%
“…In another study, it was reported that salt stress greatly inhibited germination in different radish cultivars, 0.50 mM salicylic acid application gave positive results in terms of germination percentage under salt stress. In the study, it was also stated that 1 mM salicylic acid application inhibited germination (Ulukapı et al, 2020). In studies conducted on different vegetables, it was found that as salinity increased, the germination rate decreased, and salicylic acid applications under salt stress increased the germination rate (Entesari et al, 2012;Dadaşoğlu and Ekinci, 2013;Akbıyık, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…In the other study investigating the effects of salicylic acid on the germination and vegetative growth properties of radish under salinity stress, the threshold value for salinity stress was determined as 150 mM NaCl (Ulukapı et al, 2020). In the current research, the effects of salinity were determined with the same salt concentration, and similarly, the effect of salt stress on germination differed according to the cultivar.…”
Section: Resultsmentioning
confidence: 80%
“…Severe salt stress can also inhibit longitudinal tuber growth, as reduced water uptake due to decreased soil osmotic potential caused by salt stress leads to cellular dehydration and loss of turgor pressure, ultimately halting growth (Zhao et al, 2021). Salicylic acid application may have acted as a protective agent against the negative effects of salt stress, allowing cells to continue elongating even under high salt concentrations (Ulukapi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Radish (Raphanus sativus L. -Brassicaceae) is classified as moderately sensitive to salt stress, and when exposed to high salt levels, it experiences a decline in photosynthetic capacity, growth, and ultimately yield (Henschel et al, 2023). Salicylic acid (Ulukapi et al, 2020;Mahdavian, 2023), methyl jasmonate (Henschel et al, 2023), gibberellic acid (Mishra et al, 2019), and polyamine (Çavuşoğlu et al, 2008) have been reported as mitigators of salt stress-induced damage in radish plants. Thus, the objective of this study was to assess the impact of phytohormone application in mitigating the harmful effects of salt stress on radish.…”
Section: Introductionmentioning
confidence: 99%